2019
DOI: 10.1002/tal.1680
|View full text |Cite
|
Sign up to set email alerts
|

The effect of plan ratios on wind interference of two tall buildings

Abstract: SummaryTall buildings are vulnerable to lateral loading. The facades of these buildings are susceptible to wind loads. It is very difficult to assess the wind condition around the tall building in the presence of other surrounding buildings due to the wind interference effect. An experiment is carried out in the Boundary Layer Wind Tunnel at Tokyo Polytechnic University, Japan, to study the wind interference effect on tall buildings with varying plan ratios. The maximum and minimum local peak pressure coeffici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…The building facades are often damaged under strong winds (Hu et al, 2017, 2019; Liang et al, 2020). Though some new methods emerge (Hu et al, 2020; Lin et al, 2021; Kim et al, 2021), wind tunnel testing is still the most favorable way to obtain the wind pressures on buildings (Sy et al, 2019; Behera et al, 2020; He et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The building facades are often damaged under strong winds (Hu et al, 2017, 2019; Liang et al, 2020). Though some new methods emerge (Hu et al, 2020; Lin et al, 2021; Kim et al, 2021), wind tunnel testing is still the most favorable way to obtain the wind pressures on buildings (Sy et al, 2019; Behera et al, 2020; He et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Behera et al (2020) carried out wind tunnel tests to examine the interference effect between buildings with various plan ratios. The peak pressure coefficients on the windward face of the principal building were analyzed.…”
Section: Introductionmentioning
confidence: 99%
“…Blocken [29] discussed the important aspect of CFD for defining urban physics and gave ten important tips and tricks towards the accurate and reliable simulations. Behera et al [30] performed an experiment in the boundary layer wind tunnel to investigate the wind interference effect on tall buildings with varying plan ratios, and observed that the interference zone extends over a larger area as the building plan ratio increases. Tamura et al [31] performed a series of wind tunnel tests to determine the aerodynamic performance and pedestrian level wind characteristics of different super tall buildings having square, rectangular, and elliptic plan with corner cuts.…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers have studied proximity effects between tall buildings [4,5,6,7,8,9,10,11,[12][13][14][15][16][17][18][19]. Behera et al [20] studied the proximity effect between high-rise buildings with different plan ratios and interfering building positions. It was observed that interference effects were beneficial with respect to the maximum positive pressure, but minimum negative pressure significantly increased.…”
Section: Introductionmentioning
confidence: 99%